2017
DOI: 10.1016/j.athoracsur.2016.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Dissection: A Case Treated by Homograft Replacement

Abstract: Pulmonary artery dissection was diagnosed in a 32-year-old man who was admitted to the emergency department with intense chest pain. He had a history of pulmonary balloon valvuloplasty for congenital pulmonary stenosis at the age of 7 and no pulmonary hypertension. The operation was performed with cardiopulmonary bypass. The dissected pulmonary arterial trunk was removed with the distorted valve, and replaced with a pulmonary artery homograft. The postoperative course was uneventful. Histologic examination rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Pulmonary artery dissection is a rare disease with a high mortality, with predominately case reports noted in the literature [1] , [2] , [3] , [4] , [5] . It most commonly occurs secondary to pulmonary arterial hypertension, but has been reported with right heart endocarditis, amyloidosis, catheterization, and chronic pulmonary artery inflammation [1] , [2] , [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary artery dissection is a rare disease with a high mortality, with predominately case reports noted in the literature [1] , [2] , [3] , [4] , [5] . It most commonly occurs secondary to pulmonary arterial hypertension, but has been reported with right heart endocarditis, amyloidosis, catheterization, and chronic pulmonary artery inflammation [1] , [2] , [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pulmonary aortic dissection is not well defined. However, medical management of resulting pulmonary hypertension, surgical repair of entry site, lobectomy, and transplantation have all been briefly described [2] , [3] , [5] . Aortic and pulmonary artery dissection should be considered in patients with chest pain or shortness of breath with any of the above risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…While heart‐lung transplantation has been described for PAH patients with PA dissection, 7,8 psychosocial factors proved a significant barrier for our patient. Excision and replacement of the dissected PA aneurysm segment has also been reported, using a prosthetic graft, 9 homograft, 10 or stentless xenograft 11 . However, there is no consensus on which technique is preferred, or at what diameter PA aneurysms should be repaired.…”
Section: Discussionmentioning
confidence: 99%
“…This might have slowed the evolution to heart failure, explaining the late symptomatology, but same criteria as for aortic aneurysms to decide surgical intervention, consisting in a diameter of more than 5,5cm, symptoms, more than 0,5cm diameter increase in 6 months, complications, etc 1 . A careful management is generally recommended, because even if the rupture risk is low, there are also other possible fatal complications that may occur, like pulmonary embolism, heart failure and compression of the surrounding structures including the coronary arteries 13 . Duijinhouwer et al concluded in a recent review and analysis that pulmonary hypertension in congenital heart disease (CHD), a fast diameter growth (>2 mm/ year), tissue weakness mostly due to infection are the most frequent predisposing factors for dissection, and in the rest of the cases, the risk is low 3 .…”
Section: Discussionmentioning
confidence: 99%